Using the Schoolwide Expectations Survey for Specific Settings to Build Expectation Matrices. (February 2019) - Lane, Kathleen Lynne; Oakes, Wendy Peia; Royer, David J.; Cantwell, Emily D.; Menzies, Holly Mariah; Jenkins, Abbie B.; Hicks, Tyler
Schoolwide expectations are a critical component of tiered systems of support, particularly when established with input from faculty and staff and then taught to all students. The expectation matrices depicting these expectations for all key settings serve as important instructional tools when teaching schoolwide expectations. In this study, we examined psychometric properties of the Schoolwide Expectations Survey for Specific Settings (SESSS)—a measure designed to assist school teams in K-12 settings constructing schoolwide expectations for seven school settings with input from all faculty and staff—with results indicating strong internal consistency of items. These settings are classrooms, hallways, cafeterias, playgrounds, restrooms, buses, and arrival/dismissal. In addition, we examined the degree to which adults in elementary, middle, and high school converged and diverged in their expectations for each setting. Using mixed-effects modeling for nested data, we found some expectations varied among school levels in some noninstructional settings. We conclude with limitations and future directions.